Molecular Characterization and Clinical Relevance of ANXA1 in Gliomas via 1,018 Chinese Cohort Patients - Qian, Zenghui; Fan, Wenhua; Meng, Fanlin; Sun, Zhiyan; Li, Guanzhang; Zhai, You; Chang, Yuanhao; Yang, Changlin; Zeng, Fan; Chai, Ruichao; Wu, Fan; Zhao, Zheng (Frontiers in Cell and Developmental Biology, 2021)
Annexin A1 (ANXA1) is a calcium-dependent phospholipid-binding protein and has been implicated in multiple functions essential in cancer, including cell proliferation, apoptosis, chemosensitivity, metastasis, and invasion. However, the biological role and clinical behavior of ANXA1 in glioma remain unclear. In this study, RNA-seq (n = 1018 cases) and whole-exome sequencing (WES) (n = 286 cases) data on Chinese cohort, RNA-seq data with different histological regions of GBM blocks (n = 270 cases), and scRNA-seq data (n = 7630 cells) were enrolled. We use the R software to do statistical calculations and graph rendering. We found that ANXA1 is closely related to the malignant progression in gliomas. Meanwhile, ANXA1 is significantly associated with clinical behaviors. Furthermore, the mutational profile revealed glioma subtypes classified by ANXA1 expression showed distinct genetic features. Functional analyses suggest that ANXA1 correlates with immune-related function and cancer hallmark. At a single-cell level, we found that ANXA1 is highly expressed in M2 macrophages and tumor cells of the mesenchymal subtype. Importantly, our result suggested that ANXA1 expression is significant with the patient’s survival outcome. Our study revealed that ANXA1 was closely related to immune response. ANXA1 plays a key factor in M2 macrophages and MES tumor cells. Patients with lower ANXA1 expression levels tended to experience improved survival. ANXA1 may become a valuable factor for the diagnosis and treatment of gliomas in clinical practice.